PENGARUH PELATIHAN PLAIOMETRIK FLOOR KIP TERHADAP KELINCAHAN DAN DAYA LEDAK OTOT TUNGKAI PADA SISWA PUTRA KELAS X SMA PGRI 1 AMLAPURA TAHUN PELAJARAN 2012/2013 - Agus Wirajaya, I Gede (Universitas Pendidikan Ganesha, 2013)
This study was aimed at proving the influence of training of the Plaiometrik Floor Kip concerning to the improvement of leg muscle explosive power. The subject of this study were the class X of SMA PGRI 1 Amlapura in academic year 2012/2013 that consist of 70 students which divided into 2 groups, there were 35 students in group of treatment and 35 students in group of control. This study used an experimental research by designed the modified randomized the pretest posttest control group design. The instrument of this study was test. The agility was measure by the zig-zag run test and the explosive leg muscle power was measure by standing broad jump test. The data were analized by using Uji-t independent at significance level 0.05. the data were analized using SPSS 16,0. The result of the data showed that there was improvement in students mean score in agility in treatment group that was 1.20 second and in control group the improvement of the mean score was 7,88 cm however the control group improve became 2,2 cm. It can concluded that plaiometrik floor kip training could improve the agility and the explosive leg muscle power. The significance improvement for agility was 0.000 (sig = 0,000), and the explosive leg muscle power was 0,000 (sig = 0,000).